From Vineyard to Label: The Evolution of Wine Label and Advertisement Design in the 1960´s in Mendoza, Argentina - Copia, María Laura (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article aims to research about the modifications and transformations in wine label design and their prominence in advertising in a context of unprecedented increase in wine production in the 1960s in the province of Mendoza, Argentina. During the decade under consideration, from 1958 to 1970, this phenomenon was strengthened by innovations in distribution channels and promotional strategies, both corporate and state-driven. Simultaneously, this period saw the emergence of Design as a disciplinary field in our province, so we seek to determine whether label design benefited from contributions from this new disciplinary field and to what extent it reflected changes in the wine industry. To achieve this, in addition to existing literature, we consulted repositories and collections of labels, as well as magazines from the period, giving particular importance to the publication "Vinos, Viñas y Frutas," published by the Argentine Viticulture Association.